Independent Evaluation of IFC's Development Results 2007 : Lessons and Implications from 10 Years of Experience - Independent Evaluation Group (2012)
IFC's overriding objective is to help reduce poverty and support sustainable development in developing countries. This report, which assesses the impact of IFC toward that mission, appears at a time of unprecedented levels of private investment in the emerging markets. The report takes a look back at the development results that IFC-supported projects have achieved in the last 10 years, the main lessons that have emerged at the project level and the strategic implications for IFC going forward, in the context of rapid organizational growth. The report finds that IFC-supported project performance is closely linked to the quality of a country's business climate, the presence of a high quality sponsor, well-managed company and product market risk, and in particular, to IFC's work quality (especially at the appraisal and structuring stage, and including oversight of the environmental and social effects of projects). Going forward, the report highlights major challenges IFC faces to achieving overall development effectiveness. IFC will need to adopt a sharper country focus and better exploit synergies with the Bank and other development partners in improving business climates in developing countries.